Primary sclerosing cholangitis: is any treatment worthwhile? - Barnabas, A; Chapman, R (2012)
While many therapeutic agents have been evaluated in Primary Sclerosing Cholangitis (PSC), none have been shown in controlled trials to modify the course of disease. The bile acid ursodeoxycholic acid (UDCA) has been widely used in the treatment of PSC but its use remains controversial. It may have a role in providing chemoprotection against the development of colonic dysplasia/cancer in patients with associated inflammatory bowel disease. The exclusion of IgG4-associated cholangitis, which generally responds to immunosuppressant agents, is essential prior to deciding on an appropriate therapeutic strategy in PSC. In the absence of proven therapeutic agents, treatment strategies are usually aimed at minimizing the complications of the biliary disease. Endoscopic management of dominant strictures may improve long-term outcomes. Orthotopic liver transplantation has a good outcome in patients with end stage PSC.